Modeling propagation of weakly advantageous mutations in cancer cells - Polański, Andrzej; Kania, Mateusz; Gil, Jarosław; Łabaj, Wojciech; Lach, Ewa; Szczęsna, Agnieszka (Zielona Góra: Uniwersytet Zielonogórski)
There is recent evidence that a considerable proportion of somatic mutations in cancer cells` DNA may exert a weakly advantageous effect on tumor growth. In this paper, we develop models of cancer evolution with somatic mutations that introduce a weakly advantageous force to the evolution of cancer cells. The elaborated models incorporate random events of cellular births, deaths and occurrences of somatic mutations in cancer cells` DNA.
Keywords: cancer evolution; Gillespie algorithm; mutation wave modeling